LTRs of Endogenous Retroviruses as a Source of Tbx6 Binding Sites - Yasuhiko, Yukuto; Hirabayashi, Yoko; Ono, Ryuichi (Frontiers in Chemistry, 2017)
Retrotransposons are abundant in mammalian genomes and can modulate the gene expression of surrounding genes by disrupting endogenous binding sites for transcription factors (TFs) or providing novel TFs binding sites within retrotransposon sequences. Here, we show that a (C/T)CACACCT sequence motif in ORR1A, ORR1B, ORR1C and ORR1D, Long Terminal Repeats (LTRs) of MaLR endogenous retrovirus (ERV), is the direct target of Tbx6, an evolutionary conserved family of T-box transcription factors. Moreover, by comparing gene expression between control mice (Tbx6 +/-) and Tbx6-deficient mice (Tbx6 -/-), we demonstrate that at least four genes, Twist2, Pitx2, Oscp1, and Nfxl1, are down-regulated with Tbx6 deficiency. These results suggest that ORR1A, ORR1B, ORR1C and ORR1D may contribute to the evolution of mammalian embryogenesis.